Exclusion of exotic top-like quarks with -4/3 electric charge using jet-charge tagging in single-lepton ttbar events at CDF - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2013)
We report on a measurement of the top-quark electric charge in ttbar events in which one W boson originating from the top-quark pair decays into leptons and the other into hadrons. The event sample was collected by the CDF II detector in sqrt(s)=1.96 TeV proton-antiproton collisions and corresponds to 5.6 fb^(-1). We find the data to be consistent with the standard model and exclude the existence of an exotic quark with -4/3 electric charge and mass of the conventional top quark at the 99% confidence level.